Additional studies on the antifungal activity of a methanol extract of Ipomoea carnea subsp. fistulosa and Octadecyl p-Coumarates - Nidiry, Eugene Sebastian John; Ganeshan, Girija; Lokesha, Ankanahalli Narayanashetty; Ramachandran, Nanjundagowda (Pharmacognosy Communications)
Background: Ipomoea carnea subsp. fistulosa is a plant native to South America, but sparsely distributed in India and Bangladesh. Aphrodisiac, purgative, cathartic and sore curing properties have been attributed to the plant. Although there were several papers on the antifungal and antibacte- rial activities of on the crude extractives of the plant, the first report on the bioassay monitored isolation and characterization of the chief antifungal compounds as a mixture of E and Z isomers of octadecyl p-coumarates was published from this Institute. Material and Methods: The methanol extractive of Ipomoea carnea subsp. fistulosa exhibited antifungal activity against the mycelial growth of Phytophthora nictotiana by poisoned food technique. This is in addition to the reported activity against Colletotrichum gloeosporioides. Results and Discussion: Octadecyl p-coumarates isolat- ed from the plant by column chromatography followed by HPLC exhibited activity against the mycelial growth of Cercospora capsici. This is in addi- tion to the reported activity of octadecyl p-coumarates against the spore germination of Alternaria alternata, Alternaria porri and Cladosporium cuc- umerinum. Conclusion: Additional studies conducted with the crude ex- tractive of Ipomoea car nea subsp. fistulosa confirmed its antifungal activity against Phytoph thora nicotianae. Identification of octadecyl p-coumarates as antifungal active principles was confirmed by its activity against Cerco- spora capsici by modified mycelial growth inhibition study.
Keywords: Ipomoea carnea subsp. fistulosa; Octadecylp-coumarates; Antifungal activity; Phytophthora nicotianae; Cercospora capsici.